'Should I stay or should I go now?': A qualitative study of why UK doctors retire. Issue 9 (2nd June 2020) - Cleland, Jennifer; Porteous, Terry; Ejebu, Ourega‐Zoe; Skåtun, Diane
Abstract : Objectives: Health care delivery and education face critical potential shortages in the foreseeable future in terms of retaining doctors nearing the time of retirement ‐ doctors who have experience‐based knowledge to pass onto the next generation. Retirement decisions are driven by a combination of macro‐related, job and individual factors. This is a constantly shifting space; findings from earlier studies do not always help us understand the retirement decisions of contemporary cohorts of doctors. To address these issues, and identify new knowledge to inform approaches to retaining expertise, we aimed to identify and explore what may keep an older doctor in the workforce ('stay') factors and ('go') factors that might prompt retirement. Methods: We invited doctors aged 50 years or over from diverse areas of Scotland to participate in qualitative, semi‐structured interviews. Initial analysis of interview transcripts was inductive. The embeddedness theory of Mitchell et al encompassing the dimensions of 'link, ' 'fit' and 'sacrifice, ' was used for subsequent theory‐driven analysis. Results: A total of 40 respondents participated. In terms of 'link, ' retiring could feel like a loss when work links were positive, whereas the opposite was true when relationships were poor, or peers were retiring. Considering 'fit, ' intrinsic job satisfaction was high but respondents had less confidence in their own abilities as they grew older. However, the data foregrounded the inverse of the notion of Mitchell et al's 'sacrifice'; for UK doctors, staying in work can involve sacrifice because of tax penalties, work intensity and arduous demands. Conclusions: Retirement stay and go factors seem enmeshed in the cultural, social and economic structures of health care organisations and countries. Systems‐level interventions that address ultimate causes, such as sufficient staffing, supportive systems, non‐punitive taxation regimes and good working conditions are likely to be most effective in encouraging doctors to continue to contribute their knowledge and skills to the benefit of patients and learners. Abstract : With so much expertise at risk of being lost to premature retirement, this study points to systems‐level issues as the most likely ways to effectively encourage highly functioning doctors to stay in the workforce.